2008
DOI: 10.1097/ccm.0b013e318186ab1b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of community and referral intensive care unit patients in a tertiary medical center: Evidence for referral bias in the critically ill*

Abstract: Patients who resided outside of our local community and who had medical admissions to the intensive care unit were more severely ill, had greater mortality rates, and had longer length of stay compared with community patients. Our findings support the existence of referral bias in critically ill medical patients at our tertiary medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In 13,017 emergent PICU admissions across 20 PICUs, patients transferred from outside healthcare systems had greater severity of illness and required more ICU related resources compared with emergent admissions from within the institution (18). Adult studies consistently observe longer ICU stays, duration of mechanical ventilation, higher ICU resource utilization, and greater mortality risk in referral patients compared to admissions from the community or inter-hospital system (1921). This “referral bias” leads to over-representation of severe disease within an inpatient study population and hinders evaluation of prevention and early recognition strategies relevant to milder disease.…”
Section: Discussionmentioning
confidence: 97%
“…In 13,017 emergent PICU admissions across 20 PICUs, patients transferred from outside healthcare systems had greater severity of illness and required more ICU related resources compared with emergent admissions from within the institution (18). Adult studies consistently observe longer ICU stays, duration of mechanical ventilation, higher ICU resource utilization, and greater mortality risk in referral patients compared to admissions from the community or inter-hospital system (1921). This “referral bias” leads to over-representation of severe disease within an inpatient study population and hinders evaluation of prevention and early recognition strategies relevant to milder disease.…”
Section: Discussionmentioning
confidence: 97%
“…In general, many studies have documented that transfer patients result in higher mortality rates and longer length of stay at the receiving hospital, and this adverse impact on outcomes is not fully accounted for by usual clinical risk factors. [36][37][38][39][40][41][42][43][44][45] Attributing responsibility for a patient's death to the first hospital protects receiving hospitals who did not have the opportunity to administer the patient's initial care, and who otherwise might be less willing to accept high-risk patients. Conversely, it makes the first hospital responsible for the ultimate outcomes of patients it transfers to another institution, even if the stay in the initial hospital was quite short (typical for myocardial infarction).…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that after full adjustment for case-mix and severity of disease, patients who lived outside the local community who were referred to a tertiary center were sicker, had higher mortality rates, and longer length of hospital stay than directly admitted patients. 13,[15][16][17] Consequently, even transfer of 1 patient per month could make an important difference to the hospital outcome. 14 In addition, a simulation study showed that a hospital with an admission rate of 25% medical intensive care unit transfer patients compared with a hospital with a 0% admission rate would have 14 excess deaths per 1000 admissions.…”
Section: Referral Biasmentioning
confidence: 99%